Auxiliary gelling material and preparation method and application thereof

By preparing a combined auxiliary gelling material of flash flammable clay and mineralized regenerated fine powder, the problems of long calcining process, high energy consumption and low efficiency of mineralized regenerated fine powder in the prior art are solved, and gelling materials with good compressive strength are achieved, and the preparation time is short and energy consumption is low.

CN116395997BActive Publication Date: 2025-03-04SHENZHEN INSTITUTE OF INFORMATION TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310448782.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-24
Publication Date
2025-03-04
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

When using engineering waste soil and recycled micro powder resource utilization, the calcination process consumes a long time and high energy consumption, and the mineralized recycled micro powder has a low efficiency and high energy consumption, resulting in its performance being lower than that of commonly used cement mixed materials.

Method used

Using a combination of flash calcined clay and mineralized regenerated fine powder, the calcined and semi-dry mineralized regenerated fine powder is used to prepare flash calcined clay and mineralized regenerated fine powder in the air, which improves the calcination efficiency and mineralization efficiency and reduces energy consumption.

Benefits of technology

It realizes auxiliary cementitious materials with good compressive strength. Its preparation consumes short time, low energy consumption and high efficiency. It can replace the use of ordinary silicate cement in large proportions, and suppresses the fluctuations in the performance of composite cement caused by engineering waste and demolition materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004196748860000101
    Figure BDA0004196748860000101
  • Figure BDA0004196748860000111
    Figure BDA0004196748860000111
  • Figure BDA0004196748860000121
    Figure BDA0004196748860000121
Patent Text Reader

Abstract

The present invention relates to the technical field of municipal engineering and building materials, and in particular to an auxiliary cementitious material and a preparation method and application thereof. The auxiliary cementitious material comprises flash-burned clay and mineralized regenerated micropowder; the preparation method of the flash-burned clay comprises pulping and filter pressing the engineering abandoned soil to obtain a mud cake, wet filtering, centrifuging, drying and grinding the mud cake in sequence to obtain clay powder, and then calcining the clay powder; the preparation method of the mineralized regenerated micropowder comprises semi-dry mineralization of the regenerated micropowder and then drying and grinding to obtain the mineralized regenerated micropowder, wherein the specific steps of the semi-dry mineralization comprise: spraying sodium hydroxide solution on the surface of the flattened regenerated micropowder for wetting, and then placing it in an environment with a relative humidity of 80% RH to 100% RH for mineralization. The auxiliary cementitious material can replace ordinary Portland cement in a large proportion, and the preparation method has low energy consumption, short time and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of municipal engineering and building materials, and in particular to an auxiliary gelling material and a preparation method and application thereof. Background Art

[0002] The sustained and rapid growth of the population in urban agglomerations has led to an increasing demand for residential and transportation infrastructure. In Shenzhen alone, the amount of engineering waste generated each year by various types of construction and municipal projects is close to 100 million tons. Therefore, the disposal and consumption of engineering waste has increasingly become a bottleneck in the construction of a "zero-waste city". Currently, the resource utilization of engineering waste is mostly to prepare building materials with cement or water glass as a binder and engineering waste as a filler.

[0003] In addition to a large amount of construction waste, urban construction also produces a large amount of building demolition materials. Some of the demolition materials can be recycled to produce recycled aggregates, but in the process of producing recycled aggregates, recycled micropowder will be produced as a by-product, accounting for about 10% to 20% by weight. Currently, the resource utilization of recycled micropowder is similar to that of construction waste, and is mostly used as filler.

[0004] At present, in addition to being used as fillers, there is also an existing technology that uses engineering waste soil by calcining it and using it as a cement admixture, but the calcination process used is time-consuming and energy-intensive. Similarly, for regenerated micropowder, in addition to being used as a filler, there is also the use of regenerated micropowder by mineralizing it with carbon dioxide and using it as a simple carbon-fixing material, cement admixture or concrete admixture. Currently disclosed carbon dioxide mineralized regenerated micropowders mostly use dry mineralization or wet mineralization, but because the mineralization reaction process involves both the diffusion of gas on the surface of the powder and the reaction between gas and powder through the medium water, the efficiency of dry mineralization is low, and the energy consumption required for wet mineralization during the mixing process is high. Although the volcanic ash activity of mineralized regenerated micropowder is higher than that of limestone, if only the mineralized regenerated micropowder is used as a cement admixture, its performance is still lower than the cement admixture currently commonly used to prepare granulated blast furnace slag powder or fly ash. Summary of the invention

[0005] In view of the above technical problems, the present invention provides an auxiliary cementitious material and a preparation method and application thereof. The auxiliary cementitious material has good compressive strength and can replace part of the cement. The preparation method has low energy consumption, short time and high efficiency.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The present invention provides an auxiliary gelling material, comprising flash-sintered clay and mineralized regenerated micro powder;

[0008] The flash-burned clay preparation method specifically comprises: pulping and filtering the engineering waste to obtain a mud cake, wet filtering, centrifuging, drying and grinding the mud cake in sequence to obtain clay powder, calcining the clay powder in a suspended state in air to obtain flash-burned clay, wherein the calcination temperature is 850° C. to 950° C., and the calcination time is 0.5s to 1.5s;

[0009] The preparation method of the mineralized regenerated micropowder specifically comprises: semi-dry mineralizing the regenerated micropowder, and then drying and grinding to obtain the mineralized regenerated micropowder. The specific steps of the semi-dry mineralization include: spraying sodium hydroxide solution on the surface of the spread regenerated micropowder to moisten it, and then placing it in an environment with a relative humidity of 80% RH to 100% RH for mineralization.

[0010] The mud cake used for preparing flash-burned clay in the present invention is composed of clay and quartz sand. Since the particle size of clay minerals is generally smaller than that of quartz sand, wet filtration can be used to remove quartz sand as much as possible, and clay minerals are filtered into the filtrate as much as possible to increase the specific gravity of clay minerals in the fine particles precipitated after centrifugation of the filtrate. The obtained clay powder contains minerals such as kaolinite, illite, montmorillonite, and quartz, and the main effective component is kaolinite. High-temperature calcination can dehydroxylate kaolinite to form metakaolin with an amorphous structure. In addition, in the preparation method of flash-burned clay provided by the present invention, the clay powder is calcined in a suspended state in the air, which increases the specific surface area of ​​the clay powder, improves the calcination efficiency, and the calcination time used is significantly shortened compared with the prior art. Compared with the calcination method of the prior art, it not only improves the preparation efficiency, but also saves more energy.

[0011] The regenerated micropowder used in the preparation of mineralized regenerated micropowder in the present invention is a byproduct of the process of producing regenerated aggregate using demolition materials, and is mainly composed of hardened cement slurry, and the main components include a small amount of unhydrated cement particles, calcium hydroxide, hydrated calcium aluminosilicate gel, calcium sulfonate, monosulfide hydrated calcium aluminate, etc. In the process of carbon dioxide mineralization, calcium hydroxide is converted into calcium carbonate, and other components are decalcified to form aluminum silicate gel, which has volcanic ash activity; calcium carbonate not only participates in the hydration reaction, but also provides nucleation sites, which plays a role in accelerating the cement hydration reaction. The preparation method of the mineralized regenerated micropowder provided by the present invention adopts a semi-dry method for mineralization. Due to the presence of a liquid sodium hydroxide solution, the dissolution of carbon dioxide in the liquid phase is accelerated, and the efficiency is higher than that of dry mineralization; and because the sodium hydroxide solution adopts a spraying method, the amount of liquid on the surface of the regenerated micropowder is less than that of wet mineralization, and carbon dioxide is more easily diffused between the surfaces of the regenerated micropowder, and there is no need for continuous stirring operation in the wet mineralization process, and the required energy consumption is lower.

[0012] In combination with the first aspect, the particle size of the particles in the mud cake is less than 2.36 mm, and the particles constituting the mud cake can be quickly dispersed below this particle size.

[0013] In combination with the first aspect, the specific steps of wet filtration, centrifugation, drying and grinding are: after the mud cake and water are evenly mixed in a mass ratio of 1:20 to 50, the filtrate is filtered through a sieve with a pore size of no more than 25 μm and the filtrate is collected, and then the filtrate is centrifuged and the fine particles in the lower layer are collected; the fine particles are air-dried to a moisture content of less than 5%, and then ground and sieved to obtain clay powder, and the sieve pore size is 75 μm.

[0014] In combination with the first aspect, the specific steps of the semi-dry mineralization include: spreading the regenerated micropowder according to a standard of a thickness of no more than 1 mm after spreading, spraying sodium hydroxide solution evenly on the surface of the spread regenerated micropowder to moisten it according to a solid-liquid mass ratio of 0.01 to 0.1, and then placing the moistened regenerated micropowder in an environment with a carbon dioxide concentration of 10% to 30%, a temperature of 20°C to 30°C, and a relative humidity of 80%RH to 90%RH for mineralization, and the mineralization time is not less than 1 hour.

[0015] Preferably, the mineralization temperature is 20° C. to 25° C., and the mineralization time is 1 h to 3 h, which can ensure that the mineralization reaction is fully carried out.

[0016] In combination with the first aspect, the concentration of the sodium hydroxide solution is 3 g / L to 5 g / L.

[0017] In combination with the first aspect, the mass ratio of the flash-burned clay to the mineralized regenerated powder is 1.5-2.2:1, preferably 2:1. By adjusting the mass ratio of the flash-burned clay and the mineralized regenerated powder in the auxiliary cementitious material, different performance requirements of the auxiliary cementitious material in different applications can be met.

[0018] The second aspect of the present invention provides a method for preparing an auxiliary cementitious material, wherein the flash-sintered clay and the mineralized regenerated powder are prepared respectively according to the above-mentioned method for preparing flash-sintered clay and the method for preparing mineralized regenerated powder, and the obtained flash-sintered clay and the mineralized regenerated powder are mixed in a mass ratio of 1.5 to 2.2:1 to obtain the auxiliary cementitious material.

[0019] The preparation method includes the preparation of flash-sintered clay and the preparation of mineralized regenerated micropowder. The preparation method of flash-sintered clay effectively improves the calcination efficiency by controlling the calcination temperature and the calcination time, and forms metakaolin with an amorphous structure. The preparation method of mineralized regenerated micropowder does not require long-term stirring, is simple to operate, and has lower energy consumption.

[0020] The third aspect of the present invention provides a use of the auxiliary cementitious material in a cementitious material. The auxiliary cementitious material is used in the preparation of a cementitious material, and the compressive strength of the obtained cementitious material is equivalent to that of ordinary Portland cement.

[0021] In combination with the third aspect, the cementitious material also includes cement.

[0022] In combination with the third aspect, the mass proportion of cement in the cementitious material is 45% to 60%.

[0023] In the cementitious material comprising the auxiliary cementitious material and cement, the main active ingredient of the flash-burned clay in the auxiliary cementitious material is metakaolin with an amorphous structure, which can dissolve hydrated aluminate ions and hydrated silicate ions under alkaline conditions, and react with calcium ions dissolved in cement to form hydrated calcium aluminosilicate gel; the main active ingredients in the mineralized regenerated micropowder in the auxiliary cementitious material are nano-calcium carbonate and aluminosilicate gel formed by decalcification of hydrated calcium aluminosilicate, which reacts with calcium ions in cement to form hydrated calcium aluminosilicate gel again; carbonate ions dissolved from nano-calcium carbonate can react with calcium ions in cement, hydrated aluminate ions dissolved in cement or metakaolin to form semi-carbon and single-carbon hydrated calcium aluminate. Therefore, the flash-burned clay and the main active ingredients of the mineralized regenerated micropowder contained in the auxiliary cementitious material have a certain synergistic effect in the cement hydration reaction.

[0024] The beneficial effects of the present invention are as follows: the preparation method of the auxiliary cementitious material provided by the present invention is short in time, low in energy consumption and high in efficiency, and the preparation of flash-burned clay and mineralized regenerated micropowder can be completed under the conditions of short time and low energy consumption. When the obtained auxiliary cementitious material is applied to cementitious materials, the performance of the composite cement obtained by mixing the auxiliary cementitious material and ordinary cement is equivalent to that of ordinary silicate cement, so the auxiliary cementitious material can replace the use of ordinary silicate cement in a large proportion; and by adjusting the ratio of flash-burned clay and mineralized regenerated micropowder in the auxiliary cementitious material, the performance fluctuation of the composite cement caused by engineering waste soil and demolition materials with complex sources can be smoothed. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] The engineering waste soil used in the embodiments and comparative examples of the present invention comes from a construction site in Nanshan District, Shenzhen City. It is dehydrated, pulped, and filtered to form a mud cake, which is filtered through a sieve with an aperture of 2 mm and air-dried. The chemical composition of the mud cake after air-drying is calculated by weight of oxides as follows:

[0027] Chemical composition Mass ratio (%) Silicon dioxide 61.2 Alumina 20.7 Iron Oxide 5.2 Potassium Oxide 3.2 Loss on ignition 9.7 .

[0028] The regenerated fine powder used in the embodiments and comparative examples of the present invention is obtained by sieving regenerated fine aggregate with a particle size of less than 2.36 mm through a 75 μm sieve in the process of producing regenerated aggregate using demolition materials. The chemical composition of the regenerated fine powder is as follows in terms of oxide weight:

[0029] Chemical composition Mass ratio (%) Calcium Oxide 32.1 Silicon dioxide 35.8 Alumina 3.2 Magnesium oxide 9.4 Sulfur trioxide 2.1 other 1.9 Loss on ignition 15.5 .

[0030] The cement used in the examples and comparative examples of the present invention is pure silicate cement, which is prepared by mixing and grinding cement clinker of P·I 42.5R grade with dihydrate gypsum, and its chemical composition is as follows in terms of oxide weight:

[0031] Chemical composition Mass ratio (%) Calcium Oxide 67.0 Silicon dioxide 18.6 Alumina 5.4 Magnesium oxide 1.3 Sulfur trioxide 3.1 Iron Oxide 3.0 other 1.6 .

[0032] The sodium hydroxide used in the embodiments of the present invention and the comparative examples is analytically pure with a purity of ≥96%; the carbon dioxide gas is high-purity gas with a purity of 99.99%; the compressed air is high-purity air with a purity of 99.999%; and the water reducer is a polycarboxylate water reducer.

[0033] Example 1

[0034] This embodiment provides a method for preparing flash-sintered clay as an auxiliary cementitious material, and the specific steps are as follows:

[0035] (1) The air-dried mud cake is mixed evenly with water at a mass ratio of 1:35 to obtain a mud slurry with fully dispersed particles;

[0036] (2) filtering the slurry through a sieve with a pore size of 25 μm to obtain a filtrate;

[0037] (3) centrifuging the filtrate at 1000 g for 10 minutes in a centrifuge, discharging the supernatant to obtain a precipitate of fine particles;

[0038] (4) air-drying the fine particles under natural conditions until the moisture content is less than 5%, grinding the particles and passing them through a 75 μm sieve to obtain clay powder;

[0039] (5) Clay powder is mixed with compressed air and sprayed into the vertical tube furnace from the top. The clay powder is dispersed in a suspended state. The temperature in the furnace is set to 900°C and calcined for 1.0 second to obtain flash-burned clay.

[0040] Example 2

[0041] This embodiment provides a method for preparing flash-sintered clay as an auxiliary cementitious material, and the specific steps are as follows:

[0042] (1) The air-dried mud cake is mixed evenly with water at a mass ratio of 1:20 to obtain a slurry with fully dispersed particles;

[0043] (2) filtering the slurry through a sieve with a pore size of 25 μm to obtain a filtrate;

[0044] (3) centrifuging the filtrate at 1000 g for 15 minutes in a centrifuge, discharging the supernatant to obtain a fine particle precipitate;

[0045] (4) air-drying the fine particles under natural conditions until the moisture content is less than 5%, grinding the particles and passing them through a 75 μm sieve to obtain clay powder;

[0046] (5) Clay powder is mixed with compressed air and sprayed into the vertical tube furnace from the top. The clay powder is dispersed in a suspended state. The temperature in the furnace is set to 850°C and calcined for 0.5s to obtain flash-burned clay.

[0047] Example 3

[0048] This embodiment provides a method for preparing flash-sintered clay as an auxiliary cementitious material, and the specific steps are as follows:

[0049] (1) The air-dried mud cake is mixed evenly with water at a mass ratio of 1:50 to obtain a slurry with fully dispersed particles;

[0050] (2) filtering the slurry through a sieve with a pore size of 25 μm to obtain a filtrate;

[0051] (3) centrifuging the filtrate at 1000 g for 10 minutes in a centrifuge, discharging the supernatant to obtain a precipitate of fine particles;

[0052] (4) air-drying the fine particles under natural conditions until the moisture content is less than 5%, grinding the particles and passing them through a 75 μm sieve to obtain clay powder;

[0053] (5) Clay powder is mixed with compressed air and sprayed into the vertical tube furnace from the top. The clay powder is dispersed in a suspended state. The temperature in the furnace is set to 950°C and calcined for 1.5 seconds to obtain flash-burned clay.

[0054] Example 4

[0055] This embodiment provides a method for preparing mineralized regenerated micropowder of auxiliary gelling material, and the specific steps are as follows:

[0056] (1) Spread the regenerated micro powder obtained by sieving with a 75 μm sieve on a stainless steel tray to a powder thickness of 1 mm;

[0057] (2) spraying 4 g / L sodium hydroxide aqueous solution at a solid-liquid mass ratio of 0.05:1 evenly on the surface of the spread regenerated micropowder to wet it;

[0058] (3) placing the wetted regenerated micropowder in an environment with a carbon dioxide concentration of 20%, a temperature of 25° C., and a relative humidity of 90% RH for reaction for 2 hours;

[0059] (4) The regenerated micropowder after the reaction is dried under natural conditions until the moisture content is less than 5%, ground and passed through a 75 μm sieve to obtain mineralized regenerated micropowder.

[0060] Example 5

[0061] This embodiment provides a method for preparing mineralized regenerated micropowder of auxiliary gelling material, and the specific steps are as follows:

[0062] (1) Spread the regenerated micro powder obtained by sieving with a 75 μm sieve on a stainless steel tray to a powder thickness of 0.8 mm;

[0063] (2) spraying 3 g / L sodium hydroxide aqueous solution at a solid-liquid mass ratio of 0.01:1 evenly on the surface of the spread regenerated micropowder to wet it;

[0064] (3) placing the wetted regenerated micropowder in an environment with a carbon dioxide concentration of 10%, a temperature of 20° C., and a relative humidity of 80% RH for reaction for 1 hour;

[0065] (4) The regenerated micropowder after the reaction is dried under natural conditions until the moisture content is less than 5%, ground and passed through a 75 μm sieve to obtain mineralized regenerated micropowder.

[0066] Example 6

[0067] This embodiment provides a method for preparing mineralized regenerated micropowder of auxiliary gelling material, and the specific steps are as follows:

[0068] (1) Spread the regenerated micro powder obtained by sieving with a 75 μm sieve on a stainless steel tray to a powder thickness of 1.0 mm;

[0069] (2) Spraying 5 g / L sodium hydroxide aqueous solution at a solid-liquid mass ratio of 0.1:1 evenly on the surface of the spread regenerated micropowder to wet it;

[0070] (3) placing the wetted regenerated micropowder in an environment with a carbon dioxide concentration of 30%, a temperature of 30° C., and a relative humidity of 100% RH for reaction for 3 hours;

[0071] (4) The regenerated micropowder after the reaction is dried under natural conditions until the moisture content is less than 5%, ground and passed through a 75 μm sieve to obtain mineralized regenerated micropowder.

[0072] Example 7

[0073] This embodiment provides an auxiliary cementitious material composed of the flash-burned clay prepared in Example 1 and the mineralized regenerated micropowder prepared in Example 4, and its application in cementitious materials. The composition ratio of the auxiliary cementitious material and the cementitious material is shown in Table 1.

[0074] Example 8

[0075] This embodiment provides an auxiliary cementitious material composed of the flash-burned clay prepared in Example 2 and the mineralized regenerated micropowder prepared in Example 5, and its application in cementitious materials. The composition ratio of the auxiliary cementitious material and the cementitious material is shown in Table 1.

[0076] Example 9

[0077] This embodiment provides an auxiliary cementitious material composed of the flash-burned clay prepared in Example 3 and the mineralized regenerated micropowder prepared in Example 6, and its application in cementitious materials. The composition ratio of the auxiliary cementitious material and the cementitious material is shown in Table 1.

[0078] Embodiments 10 to 12

[0079] This embodiment provides an auxiliary cementitious material composed of the flash-burned clay prepared in Example 1 and the mineralized regenerated micropowder prepared in Example 4, and its application in cementitious materials. The composition ratio of the auxiliary cementitious material and the cementitious material is shown in Table 1.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing flash-calcined clay, and the specific steps are similar to those of Example 1, except that the calcination condition of the clay powder is calcined at 800° C. for 2 hours.

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing dry-process mineralized regenerated micropowder, and the specific steps are as follows: the regenerated micropowder is flattened in a stainless steel tray with a powder thickness of 1.0 mm, and is placed in an environment with a carbon dioxide concentration of 20%, a temperature of 25°C, and a relative humidity of 60% RH for reaction for 2 hours to obtain dry-process mineralized regenerated micropowder.

[0084] Comparative Example 3

[0085] This comparative example provides a method for preparing semi-dry mineralized regenerated micropowder, and the specific steps are similar to those of Example 4, except that the sodium hydroxide solution is replaced by pure water for spraying to obtain semi-dry mineralized regenerated micropowder (water spraying).

[0086] Comparative Examples 4 to 7

[0087] Comparative Examples 4 to 7 provide 4 kinds of cementitious materials, wherein the calcined clay used in Comparative Example 5 is prepared from Comparative Example 1, the calcined clay and dry-process mineralized regenerated micropowder used in Comparative Example 6 are prepared from Comparative Example 1 and Comparative Example 2, respectively, and the semi-dry-process mineralized regenerated micropowder (water spraying) and flash-burned clay used in Comparative Example 7 are prepared from Comparative Example 3 and Example 2, respectively. The composition ratios of the cementitious materials in Comparative Examples 4 to 7 are shown in Table 1.

[0088] Table 1 Component ratio of the gelling materials in Examples 7 to 12 and Comparative Examples 4 to 7

[0089]

[0090] Test Example 1

[0091] X-ray diffraction analysis was performed on the flash-sintered clays obtained in Examples 1 to 3 and the calcined clay obtained in Comparative Example 1 by adding 20% ​​zinc oxide powder. The results are shown in Table 2.

[0092] Table 2 X-ray diffraction results of Examples 1 to 3 and Comparative Example 1

[0093] Examples Amorphous content (%) Example 1 26.9 Example 2 21.8 Example 3 33.2 Comparative Example 1 39.6 .

[0094] From the test results in Table 2, it can be seen that Examples 1 to 3 adopt the flash burning method. Although kaolinite cannot be completely converted into metakaolin due to the short calcination time, the efficiency and energy consumption of flash burning are still greatly superior to ordinary calcination. Compared with Example 2, the amorphous content in Example 3 is greatly increased, indicating that within a certain temperature and time range, higher temperature and longer calcination time are conducive to the conversion of kaolinite into metakaolin.

[0095] Test Example 2

[0096] Thermogravimetric analysis was performed on the mineralized regenerated micropowders prepared in Examples 4 to 6, the dry mineralized regenerated micropowders prepared in Comparative Example 2, and the semi-dry mineralized regenerated micropowders (water spraying) prepared in Comparative Example 3, respectively. The results are shown in Table 3.

[0097] Table 3 Thermogravimetric results of Examples 4 to 6 and Comparative Examples 2 to 3

[0098]

[0099] It can be seen from the test results in Table 3 that the mineralization efficiency of Examples 4 to 6 using the semi-dry mineralization method is significantly improved compared with the mineralization efficiency of Example 2 using the dry mineralization method, and the semi-dry mineralization efficiency of Example 3 using pure water to wet the regenerated micropowder is also improved, indicating that spraying a certain concentration of sodium hydroxide solution on the regenerated micropowder for semi-dry mineralization solidifies more carbon dioxide.

[0100] Compared with Example 5, the calcium carbonate content in Example 6 is increased, indicating that within a certain humidity range and mineralization time, higher humidity and longer mineralization time are beneficial to the phase transformation of cement stone into calcium carbonate.

[0101] Test Example 3

[0102] The cementitious materials provided in Examples 7 to 12 and Comparative Examples 4 to 7 were mixed with water at a water-to-binder mass ratio of 0.35 to prepare cement paste, and a water reducer accounting for 0.5% of the weight of the cementitious material was added. The mechanical strength of the obtained cement paste was tested, and the results are shown in Table 4.

[0103] Table 4 Mechanical properties of cement paste corresponding to the gel materials of Examples 7 to 12 and Comparative Examples 4 to 7

[0104]

[0105] It can be seen from the data in Table 4 that in Examples 7 to 9, as the effective ingredients in the auxiliary cementitious materials increase, the mechanical properties of the net slurry are slightly improved. Despite this, the particle filling effect of the auxiliary cementitious materials still makes a great contribution to the strength. Compared with Example 7, although the proportion of cement in the cementitious materials in Examples 10 and 12 is reduced, resulting in a decrease in the strength of the net slurry, the amount of cement is reduced, and the strength of the net slurry obtained can still meet the use requirements; the reduction in the proportion of flash-burned clay in the auxiliary cementitious materials of Example 11 reduces the early strength of the net slurry, indicating that the ratio of flash-burned clay to mineralized regenerated micropowder has an impact on its synergistic effect.

[0106] In addition, except for Example 10, the mechanical properties of the pure silicate cement paste in the remaining examples and Comparative Example 4 are not significantly different or are slightly improved, indicating that the composite cement prepared by the auxiliary cementitious material is equivalent to that of pure silicate cement in performance; compared with the limestone calcined clay cement in Comparative Example 5, although there is no significant difference in strength, the mineralized regenerated micropowder replaces the natural raw materials, and the preparation process solidifies the carbon dioxide, which has an advantage in reducing the carbon footprint of cementitious materials; Compared with Comparative Example 5, Comparative Example 6 has a relatively low effective ingredient in the dry mineralized regenerated micropowder, and the synergistic effect with calcined clay is weak, which has a greater impact on the early strength of the paste; In Comparative Example 7, the auxiliary cementitious material includes semi-dry mineralized regenerated micropowder (water spraying), and due to the relatively low content of effective ingredients, the early strength of the paste is reduced compared with Example 8.

[0107] The above analysis shows that the mechanical properties of the cementitious material obtained by compounding the auxiliary cementitious material provided by the present invention with cement are comparable to those of pure Portland cement as the cementitious material, indicating that the auxiliary cementitious material provided by the present invention can replace the use of ordinary Portland cement to a large extent.

[0108] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An auxiliary gelling material, characterized in that: Includes flash-burned clay and mineralized recycled micro powder; The flash-burned clay preparation method specifically comprises: subjecting engineering waste soil to pulping and filter pressing to obtain mud cake, subjecting the mud cake to wet filtration, centrifugation, drying and grinding in sequence to obtain clay powder, and calcining the clay powder in a suspended state in air to obtain flash-burned clay, wherein the calcination temperature is 900° C. to 950° C., and the calcination time is 1.0 s to 1.5 s; The preparation method of the mineralized regenerated micropowder specifically comprises: semi-dry mineralizing the regenerated micropowder, and then drying and grinding to obtain the mineralized regenerated micropowder. The specific steps of the semi-dry mineralization comprise: spraying a sodium hydroxide solution on the surface of the spread regenerated micropowder to moisten it, and then placing it in an environment with a carbon dioxide concentration of 10% to 30%, a temperature of 20 to 30°C, and a relative humidity of 80%RH to 100%RH for mineralization for 1 to 3 hours.

2. The auxiliary gelling material according to claim 1, characterized in that: The particle size of the particles in the mud cake is less than 2.36 mm.

3. The auxiliary gelling material according to claim 1 or 2, characterized in that: The specific steps of wet filtration, centrifugation, drying and grinding are: after the mud cake and water are uniformly mixed in a mass ratio of 1:20-50, filtering with a sieve with a pore size of no more than 25 μm and collecting the filtrate, then centrifuging the obtained filtrate and collecting the lower layer of fine particles precipitate; air-drying the fine particles precipitate to a moisture content of less than 5%, and then grinding and sieving to obtain clay powder.

4. The auxiliary gelling material according to claim 1, characterized in that: The specific steps of the semi-dry mineralization include: spreading the regenerated micropowder according to a standard thickness of no more than 1 mm after spreading, spraying sodium hydroxide solution evenly on the surface of the spread regenerated micropowder to moisten it according to a solid-liquid mass ratio of 0.01-0.1, and then placing the moistened regenerated micropowder in an environment with a carbon dioxide concentration of 10%-30%, a temperature of 20°C-30°C, and a relative humidity of 80%RH-90%RH for mineralization, and the mineralization time is 1-3 hours.

5. The auxiliary gelling material according to claim 1 or 4, characterized in that: The concentration of the sodium hydroxide solution is 3g / L~5g / L.

6. The auxiliary cementitious material according to claim 1, characterized in that: The mass ratio of the flash-sintered clay to the mineralized regenerated micropowder is 1.5-2.2:

1.

7. A method for preparing an auxiliary gelling material, characterized in that: According to the preparation method of the flash-sintered clay in the auxiliary cementitious material according to any one of claims 1 to 5 and the preparation method of the mineralized regenerated powder, flash-sintered clay and mineralized regenerated powder are prepared respectively, and the obtained flash-sintered clay and mineralized regenerated powder are mixed in a mass ratio of 1.5 to 2.2:1 to obtain the auxiliary cementitious material.

8. Use of the auxiliary gelling material according to any one of claims 1 to 5 or the auxiliary gelling material prepared by the preparation method according to claim 7 in gelling materials.

9. The use according to claim 8, characterized in that The cementitious material also includes cement.

10. The use according to claim 9, characterized in that The mass proportion of cement in the cementitious material is 45% to 60%.

Citation Information

Patent Citations

  • Calcined clay, preparation method thereof, and limestone calcined clay cement

    CN111875268A

  • Method for preparing recycled concrete product by utilizing and sealing carbon dioxide

    CN112939538A